Quasi-static and blast resistance performance of octet-truss-filled double tubes - Lv, Weitao; Li, Dong (Engineering structures, 2023)
•An octet-truss-filled double tubes structure was presented by filling an octet-truss core into double tubes.•The octet-truss-filled double tubes has the best performance compared with the foam-filled and honeycomb-filled.•The effects of plate thickness and the side length of octet-truss on blast resistance performance were discussed. Thin-walled filled tube is a common energy absorbing and buffering structure. In this study, an octet-truss-filled double tubes structure was presented by filling an octet-truss core into double tubes. The quasi-static mechanical behavior of the octet-truss-filled double tubes was analyzed by both FEM and experiment and the blast resistance performance of the composite sandwich panel (CSP) with proposed octet-truss-filled double tubes core was analyzed by FEM. For comparison, the mechanical behaviors of random closed-cell foam-filled double tubes and square honeycomb-filled and hexagon honeycomb-filled double tubes were also studied. Results show that the specific energy absorption (SEA) value of octet-truss-filled double tubes under quasi-static was 49.5%, 19.0%, 18.4% and 8.7% higher than empty single outer tube, the empty double tubes, the random closed-cell foam-filled double tubes and the square honeycomb-filled and hexagon honeycomb-filled double tubes. In the blast resistance study, the proposed structure was simplified and arrayed to study its performance in the blast resistant CSP by numerical simulation. The maximum displacement of the midpoint of the back plate of the octet-truss-filled double tubes was 30%, 19.2%, 11.2% and 8.9% smaller than the maximum value of the CSP with single tube core, the CSP with double tubes core, the CSP with random closed-cell foam-filled double tubes core and the square honeycomb-filled and hexagon honeycomb-filled double tubes core. The effects of equivalent explosion load, plate thickness and side length of octet-truss on the blast resistance performance of the CSP were discussed. This study provides a fresh idea for the design of more efficient energy absorption and blast resistant structure.